The Effects of Mindful Attention on Cold Pressor Pain in Children - Mark Petter; Christine T Chambers; Jill MacLaren Chorney (Pain Research and Management)
BACKGROUND: Typical interventions for acute pain in children attempt to reduce pain by directing attention away from pain. Conversely, mindfulness involves devoting attention to one’s experience in an accepting and nonjudgmental way. However, the effect that instructing children to mindfully devote attention to acute pain has on pain outcomes is unknown.